2009
DOI: 10.2106/jbjs.h.01126
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing Factors for Recurrent Shoulder Dislocation After Arthroscopic Treatment

Abstract: Patients who are more likely to have a redislocation following arthroscopic repair of an anterior shoulder dislocation can be identified preoperatively on the basis of sex, age, and the time from the first dislocation to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
137
6
13

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(168 citation statements)
references
References 27 publications
12
137
6
13
Order By: Relevance
“…Various risk factors for recurrence have been mentioned in the literature for both techniques [8,12,16,26]. There is particular emphasis laid on glenoid and humeral bone lesions, history of instability, age, sex, hyperlaxity, and type or level of sports [2].…”
Section: Introductionmentioning
confidence: 99%
“…Various risk factors for recurrence have been mentioned in the literature for both techniques [8,12,16,26]. There is particular emphasis laid on glenoid and humeral bone lesions, history of instability, age, sex, hyperlaxity, and type or level of sports [2].…”
Section: Introductionmentioning
confidence: 99%
“…11 The reported risk factors for recurrent anterior stability include glenoid bone loss, large Hill-Sachs lesions and the use of less than three anchors. 5,[10][11][12][13][14][15][16][17][18] Such risk factors were identified on pre-operative, and not postoperative, MR arthrograms, and it is unclear whether postoperative structural integrity of the anteroinferior labrum as demonstrated on MR arthrogram post repair can predict clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, arthroscopic Bankart repair was not used in patients with large Hill Sachs lesion or in patients with glenoid defect greater than 25%. These patients were treated with open surgical methods such as Laterjet Method [3,4].…”
Section: J Nov Physiothermentioning
confidence: 99%
“…The studies showed that increased number of pre-operative dislocations, period between injury and surgery and increased rate of anterior translation did not adversely affect post-operative outcomes. Mobilizing the anterior capsuloligamentous complex precisely from the glenoid neck, then shifting upward and towards the lateral, and fixation with an appropriate number of anchors provided successful arthroscopic outcomes [3,7].…”
Section: J Nov Physiothermentioning
confidence: 99%
See 1 more Smart Citation